Systematic Study ofEleutherine palmi/olia (L.) Merr. (Iridaceae) of Sarawak - Nor Azila, A.Aziz (Universiti Malaysia Sarawak (UNIMAS), 2014)
E. palmifoUa (L.) Merr. is a perennial herb belongs to the monocotyledon family of Iridaceae. This species is widely used by the local peoples in Kalimantan, Indonesia as traditional medicinal herbs. This present study was conducted to determine the morphological characteristics of the vegetative parts, micro-morphological features of the leaves and also to obtain preliminary phytochemical data. The vegetative characteristics for leaves, roots, and bulbs were described in details. Scanning Electron Microscope has been used for the micro-morphological study and it was found that the stomata presence is amphistomatic and was distributed on both leaf surfaces. The type of stomata identified to be sunken and anomocytic. There is also presence of flaky waxes on both leaf surfaces. Preliminary phytochemical screening based on Harborne (1973) was conducted for the leaves and bulb of this E. palmifoUa using methanol and ethanol extract. The study had positively showed the presence of phenol, tannin, flavonoid, terpenoid, alkaloid and also protein xanthoprotein in both extract of the leaves and bulbs. However, saponin was only detected in the methanol extract. There were 6 spots observed in the two dimensional paper chromatographic of the bulbs while only 5 spots were obtained from the leaves. The tentative identification of spots showed the presence of the anthocyanin, isoflavones and flavonol in the bulbs while flavonol, isoflavone and flavone were detected in the leaves of this species. The results of this study are very important for taxonomical information and for further investigation as this species have been known to be a very potential traditional medicinal herb in Indonesia for antifungal, antiviral, antitumor, anticancer and also for diabetes mellitus.